2005
DOI: 10.4310/hha.2005.v7.n1.a8
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of racks and quandles

Abstract: A rack is a set equipped with a bijective, self-right-distributive binary operation, and a quandle is a rack which satisfies an idempotency condition.In this paper, we introduce a new definition of modules over a rack or quandle, and show that this definition includes the one studied by Etingof and Graña [9] and the more general one given by Andruskiewitsch and Graña [1]. We further show that this definition coincides with the appropriate specialisation of the definition developed by Beck [3], and hence that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…The natural coefficients for Quillen cohomology in general are the Beck modules. In the case of racks and quandles, these Beck modules have already been discussed by Jackson [15]. In the prequel [34] to this paper, we showed that a canonical refinement of the Alexander module of a knot, the Alexander-Beck module, detects the unknot.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…The natural coefficients for Quillen cohomology in general are the Beck modules. In the case of racks and quandles, these Beck modules have already been discussed by Jackson [15]. In the prequel [34] to this paper, we showed that a canonical refinement of the Alexander module of a knot, the Alexander-Beck module, detects the unknot.…”
Section: Introductionsupporting
confidence: 54%
“…Let M be an X-module in the sense of Beck. (We refer again to [15] and [34] for the theory of Beck modules with an emphasis on racks and quandles.) In other words, that X-module M is an abelian group object in the slice category T X .…”
Section: Quillen Cohomology and Extmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex is the same as the one defined in [Jac05], but in the left rack context. Adapting the proof given by N. Jackson in [Jac05], one easily sees that the second cohomology group HR 2 (X, A) is in bijection with the set of equivalence classes of abelian extensions of a pointed rack X by a X-module A. An abelian extension of a pointed rack X by a X-module A is a surjective pointed rack homomorphism E p X which satisfies the following axioms (E 0 ) for all x ∈ X, there is a simply transitively right action of A on p −1 (x).…”
Section: Pointed Rack Cohomologymentioning
confidence: 99%
“…Many variations of this idea exist, including the quandle homology described in [3], the twisted quandle homology described in [4], the quandle homology with coefficients in a quandle module ( [1], [10]), the biquandle version known as YangBaxter homology ( [5]), and a unifying approach to the homology of quandles and Lie algebras ( [2]). …”
Section: Yang-baxter Cohomologymentioning
confidence: 99%